RELATIONSHIP BETWEEN NUMERICAL ABILITY, ATTENTION OF PARENTS AND INTEREST IN LEARNING WITH RESULTS OF STUDENT LEARNING MATHEMATICS OF CLASS VII - Latifah Fitriasari; Suparyan Suparyan (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Based on information from SMP Negeri 15 Yogyakarta, low numerical abilities, lack of parental attention and low student learning interest. This study aims to determine whether there is a positive and significant relationship between numerical ability, parental attention and interest in learning with mathematics learning outcomes of class VII students of SMP Negeri 15 Yogyakarta even semester 2015/2016 academic year. The population in this study were all regular VII grade students of SMP Negeri 15 Yogyakarta even semester 2015/2016 academic year as many as 5 classes. Class VII C was taken as the research sample class with a random sampling technique for the class. Data collection techniques in the form of questionnaires and test techniques. The research instrument was in the form of a questionnaire for variables of parental attention and variables of interest in learning while the research instruments were in the form of tests for numerical ability variables and mathematics learning outcomes variables. Test of research instruments used validity tests, different power tests, and reliability tests. Analysis prerequisite test includes a normality test, independent test and linearity test. Data analysis for hypothesis testing using product-moment correlation analysis and multiple linear regression analysis. The results showed a positive and significant relationship between (1) the numerical skills with mathematics learning outcomes, with r = 0.4176780979; (2) The parent's attention  with mathematics learning outcomes, with r = 0.4826111448; (3) interest in learning with mathematics learning outcomes, with r = 0.2873655253; (4) The numerical skills and parents attention with math learning outcomes, with R = 0.5921931342; (5) The numerical skills and interest in learning with mathematics learning outcomes, with R = 0.4314264425; (6) The parents attention and interest in learning with mathematics learning outcomes with R = 0.5623422638; (7) The numerical skills, parents attention and interest in learning with mathematics learning outcomes, with R = 0.609887925 and the linear regression equation Y = -14.81581646 + 0.2860704335 + 0.7994211603 + 0.2860704335 . Large donations are relatively  = 30.35,  = 56.92% and  = 12.73% and the effective contribution  = 11.29%, = 21.17% and = 4.73%.